Introduction to flexible, adaptive trial design - Mehta, Cyrus (Henry Stewart Talks, 2007)
Advantages of flexible clinical trials, Group sequential designs, Information based designs, Applications and logistical aspects of information based designs, Adaptive designs, Flexibility of the adaptive methods, Sample size computation, Group sequential or adaptive trial re-design due to the occurrence of unforeseen events, Flexible trial designs and the FDA's Critical Path Initiative
Archived at 2018/05/31